Tradition and transition of Malaysian society across time - Abdullah, Muhammad Hussein; Subramaniam, Vijayalectumy; Wan Jaafar, Wan Munira; Elangkovan, Kaviyarasu (Mediterranean Center of Social and Educational Research, 2013)
Tradition is a ritual, belief or subject passed down within a society. They illustrate the identity of a society, and it is still maintained until today. Polemic appears generally when tradition is urged within time frame, where it eliminates the flow of tradition from older generation to present generation. Tradition is an asset of society which is related with ancient history therefore invented on purpose. Transition in tradition that took place in Malaysian context begins when British Colonial brings in migrants from India and China to work in Malay Federation which eventually formed a multiracial society in Malaysia. Malaysian society has undergone many phases of situation either political or policy change with in the state that lead to culture accommodation among different ethnics. Acculturation also took place whereby the difference or uniqueness of a culture is combined with another cultures from different ethnic. The time frame had been the most prominent factor for the overall changes in the world.